Effect of APM treatment on strength properties of Hevea brasiliensis(Rubber wood) - Shukla N K; Khanduri A K; Satish Kumar (Journal of the Timber Development Association(India), 1993)
In order to save the energy in seasoning prior to preservative treatment the alternate pressure method(APM) to treat the green wood is gaining importance. This paper deals with the effect of APM treatment with Borax:Boric acid composition on the strength properties of Hevea brasiliensis (rubberwood). Most of the strength properties of rubberwood remained unaffected by this treatment method.
Keywords: APM treatment; Rubberwood